PEMANFAATAN APLIKASI iPUSNAS OLEH PEMUSTAKA DI UPT PERPUSTAKAAN PROKLAMATOR BUNG KARNO - Gambiro, Indrawan; Kurniawati, Shanti Tri; Yohane, Ide (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2024)
This study aims to determine the level of knowledge of users at the UPT Bung Karno Library on theiPusnas Application of the National Library of Indonesia. This study took a sample of 303 respondents.The research method used is descriptive qualitative method. Data collection is done by questionnaire,observation, and documentation. The results of this study show that out of 303 respondents it isknown that 39% or 118 people already know the iPusnas application and 61% or 185 people do notknow the iPusnas application. Of the 118 respondents who know the iPusnas application, 65% or 77people have downloaded the iPusnas application and 35% or 41 people have not downloaded theiPusnas application. From the data from this study it can be seen that many users at the Bung KarnoProclamator Library still do not know about iPusnas. Therefore it is necessary to increase thesocialization and promotion of the iPusnas application through social media, the web, and on sitethrough the user guidance program.